La SF de la Théorie : Baudrillard et Haraway - Istvan Csicsery-Ronay (Jr.) (ReS Futurae)
With the expansion of the technological construction of social life in the postmodem period, SF ceases to be a genre of art and becomes instead a mode of quotidian awareness. At the heart of this mode are two hesitations : a) about whether scientific-technological transformations are merely conceivable or actually realizable, and b) about the possible implications of their realization. As previously barely imaginable social conditions emerge through the effects of technology-particularly informatic technology-the objects of cultural theory become concrete, and theoretical reflection about their future becomes indistinguishable from SF. Jean Baudrillard and Donna Haraway are two of the most acute theorists in the SF mode. Baudrillard argues that in the age of hyperreality, no distance remains between reality and the imaginary models used to conceive it. Science fiction, the type of imaginary model appropriate for the bourgeois-productionist phase of history, ceases to exist when reality surpasses it. Haraway proposes the notion of the cyborg as a revolutionary being, simultaneously defined by technology and by emancipatory aspiration. Both theorists elaborate SF topoi, while writing theory that is poised between fiction and rational explanation-just like SF.